Multifunctional flexible composite protection structure and preparation method thereof

Through the flexible composite protective structure of a multi-layer structure, combined with nanofiber aerogel and silica aerogel, the problem of difficulty in taking into account the protective performance, flexibility and stealth camouflage of individual protective equipment is solved, and the effects of infrared stealth and impact protection are achieved.

CN119795720AActive Publication Date: 2025-04-11CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411769694.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

Existing individual protective equipment is difficult to take into account the functions of protective performance, flexibility, stealth camouflage, etc., especially during nighttime penetration.

Method used

A flexible composite protective structure with a multi-layer structure is adopted, including nanofiber aerogel phase change composite film, nanofiber aerogel film, silica aerogel composite fiber felt and shear hardening/aramid protection main structure. It is cured between the fluorocarbon resin spray coating layers to form a lightweight, flexible, bulletproof, infrared thermal radiation barrier protective structure.

Benefits of technology

It has achieved the purpose of blocking the human body's heat and limiting the dissipation of infrared thermal radiation. Under infrared thermal imaging, the target is consistent with the temperature of the external ambient, which improves the stealth and safety of individual combat, and also has good impact protection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795720A_ABST
    Figure CN119795720A_ABST
Patent Text Reader

Abstract

The invention provides a multifunctional flexible composite protection structure and a preparation method thereof, and the composite protection structure sequentially comprises a nanofiber aerogel phase change composite film (KNA / PEG), a nanofiber aerogel film (KNA), a silicon dioxide aerogel composite fibrofelt and a shear hardening / aramid fiber (SSE / Kevlar) protection main body structure from the outer layer to the inner layer, the shear hardening / aramid fiber protection main body structure is obtained by stacking a plurality of layers of shear hardening precursor Kevlar prepregs and then carrying out heat treatment. The multifunctional flexible composite protection structure disclosed by the invention has the advantages of extremely low heat conductivity coefficient, low density, flame retardance, low infrared emissivity, flexibility and impact protection, and can block heat of soldier bodies and limit infrared heat radiation emission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of human body protection equipment, and specifically relates to a multifunctional flexible composite protection structure and a preparation method thereof. Background Art

[0002] In the confrontation pattern of modern battlefields, large-scale firepower conflicts of soldiers are no longer the main combat method, but mainly reconnaissance raids by a small number of soldiers. This puts higher requirements on the camouflage, stealth and other functions of individual protective equipment. Especially during the night breakthrough, the heat source radiation signal of the soldiers is the most significant feature, which can easily cause the exposure of the soldiers' position information. Therefore, in modern warfare, it is particularly important to reduce the infrared special radiation emission of equipment and confuse the enemy's infrared detection. Infrared stealth technology is particularly important. At the same time, for individual protective equipment, hard protective equipment is usually heavy and poorly wearable, which is not conducive to long-term wear and long-distance marching. Therefore, the research and development of lightweight and flexible individual equipment is very necessary. Therefore, while taking into account the protective performance, individual protective equipment is lightweight, flexible and stealth camouflage, which is of great significance for future battlefield raids.

[0003] Shear hardening material (SSE) is a strain rate sensitive adaptive material. Its energy storage indexes such as viscosity, storage modulus, loss modulus, and damping loss factor are closely related to the external strain rate environment. It behaves as a viscous fluid or elastomer under static or low strain rate load. When subjected to high strain rate load, the material changes phase to solid state, thereby absorbing a large amount of impact energy and improving protective performance. Aramid fiber fabrics have the advantages of high strength, high modulus, good stability, and certain flame retardant properties. They are often used in the field of protection. Due to the strain rate adaptive advantage of SSE materials, their composite with bulletproof woven fabrics can significantly enhance the fabric's interface friction, impact energy absorption, and ballistic limit. Compared with pure fabric protective structures with the same surface density level, the impact deformation is smaller, and it has great impact protection advantages.

[0004] According to the Stefan-Boltzmann law, the infrared thermal radiation intensity per unit area of ​​an object is proportional to its surface infrared emissivity and the fourth power of its temperature. Therefore, the infrared radiation of an object can be reduced by regulating the infrared emissivity and lowering the temperature, and the cooling measures are more effective. Aerogel material is a lightweight, sparse, porous material. The internal volume is almost entirely filled by air. It is the lightest known material. The extremely low thermal conductivity of air gives aerogel material good thermal insulation properties. However, the low mechanical properties of aerogel materials severely limit their applicability. They are prone to breakage, shedding, and other failures, resulting in a serious decline in performance. Summary of the invention

[0005] In order to solve the problem that individual soldier protective equipment in the prior art cannot take into account protective performance, flexibility, stealth camouflage, etc., the present invention provides a multifunctional flexible composite protective structure and a preparation method thereof, which has extremely low thermal conductivity, low density, flame retardancy, low infrared emissivity, flexibility and impact protection, can block the heat of the soldier's body and limit the emission of infrared thermal radiation, make the target consistent with the background temperature of the external environment under infrared thermal imaging, and well integrate the thermal appearance of the target into the background; maintain a certain flexibility of the composite protective structure, can adapt to the bending activities of the human body during wearing, and quickly harden after being impacted by a bullet, significantly enhance the impact energy absorption and limit impact deformation, thereby achieving the purpose of protecting the human body.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] The first purpose of the present invention is to provide a multifunctional flexible composite protective structure, which includes, from the outer layer to the inner layer, a nanofiber aerogel phase change composite film (KNA / PEG), a nanofiber aerogel film (KNA), a silica aerogel composite fiber felt, and a shear hardening / aramid (SSE / Kevlar) protective main body structure. The shear hardening / aramid protective main body structure is obtained by stacking multiple layers of shear hardening precursor Kevlar prepreg and then heat treating them.

[0008] The second object of the present invention is to provide a method for preparing a multifunctional flexible composite protective structure, comprising the following steps: arranging a nanofiber aerogel phase change composite film, a nanofiber aerogel film, a silica aerogel composite fiber felt, and a shear hardening / aramid protective main body structure in sequence, and spraying a fluorocarbon resin mixed with a B1540 curing agent between the layers, and curing and molding to obtain the structure;

[0009] The nanofiber aerogel phase change composite film is obtained by melting the thermal phase change material PEG at high temperature and adsorbing it through the microscopic capillary force of the KNA film;

[0010] The shear hardening / aramid protective main structure is prepared by uniformly mixing the prepared shear hardening glue with methyl vinyl silicone rubber and a vulcanizer, adding white carbon black and pressing the film at 60°C, laying the obtained film flat on the surface of the Kevlar braid and compounding it with double rollers to obtain a shear hardening precursor Kevlar prepreg, and then obtaining it through variable angle laying and stacking between layers and hot pressing molding.

[0011] Furthermore, the preparation method of the nanofiber aerogel membrane is: dispersing aramid staple fibers in a dimethyl sulfoxide solution, then adding a strong base to form an alkaline environment, obtaining a nanofiber dispersion after a sufficient sol process, then obtaining a nanofiber hydrogel after replacement with deionized hydrogel, anhydrous ethanol and tert-butanol, and then freeze-drying to obtain a nanofiber aerogel membrane.

[0012] Furthermore, the mass ratio of the added aramid staple fibers to dimethyl sulfoxide is 1.5-2.5:97.5-98.5.

[0013] Furthermore, the mass of the added strong base is 1% of the mass of the mixed solution.

[0014] Furthermore, the nanofiber dispersion is scraped to form a sol film, then immersed in deionized water for replacement to form a gel film, and the residual dimethyl sulfoxide and protonate are removed, and then enters a mixed solution of anhydrous ethanol and tert-butyl alcohol for solvent replacement to obtain a nanofiber hydrogel.

[0015] Furthermore, the freeze-drying time is 48 to 72 hours.

[0016] Furthermore, the preparation method of the silica aerogel composite fiber felt is as follows: a silicon source, anhydrous ethanol and deionized water are mixed in proportion and the pH value is adjusted to 3-4, a hydrolysis reaction is carried out, after the hydrolysis is completed, the pH value of the solution is adjusted to 6-7 for a condensation reaction, before the gelation, aluminum silicate ceramic fiber felt is added and placed in a closed container to form a gel, and the gel is aged, replaced, modified, and replaced and dried to obtain the silica aerogel composite fiber felt.

[0017] Furthermore, the molar ratio of the silicon source to anhydrous ethanol and deionized water is 1:6-10:2-6.

[0018] Furthermore, the acid used to adjust the acidic environment is dilute hydrochloric acid, and the alkali used to adjust the alkaline environment is aqueous ammonia.

[0019] Furthermore, the volume ratio of ammonia water to anhydrous ethanol is 1:30.

[0020] Furthermore, the silicon source is selected from ethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, isopropyl orthosilicate, methyltriethoxysilane or ethyltrimethoxysilane.

[0021] Furthermore, the temperature of the hydrolysis reaction and the polycondensation reaction is 25 to 35°C.

[0022] Furthermore, the gel aging is performed by immersing the formed gel in a mixed solution of a sufficient amount of silicon source and anhydrous ethanol, and the volume ratio of the silicon source to the anhydrous ethanol during aging is 1:5.

[0023] Furthermore, the replacement is to immerse the aged gel in anhydrous ethanol, and the modification is to place the replaced gel in a sufficient amount of modification liquid for modification for 8 to 24 hours, wherein the modification liquid is a mixture of a modifier and anhydrous ethanol, and the modifier is hexamethyldisilazane, trimethylchlorosilane, dimethyldichlorosilane or methyltrichlorosilane.

[0024] Furthermore, the preparation method of the shear hardening glue is: after fully dissolving the boric acid with isopropanol, adding hydroxy silicone oil and stirring evenly, then heating at 150-200° C. to volatilize the isopropanol, placing it in a vacuum kneader after the volatilization is completed to carry out a polymerization reaction, and the shear hardening glue is obtained after the mixture becomes a viscous polymer with a silk-like luster.

[0025] Furthermore, the ratio of boric acid to hydroxy silicone oil is 1 ml:50 mg.

[0026] Furthermore, the polymerization reaction conditions are 200-250° C., 1.5-2.5 h.

[0027] Furthermore, the mass ratio of the shear hardening rubber, methyl vinyl silicone rubber and vulcanizing agent is 70:30:1.

[0028] Furthermore, the vulcanizing agent is benzoyl peroxide.

[0029] Furthermore, the amount of white carbon black added is 15% of the total colloid mass.

[0030] Furthermore, the thickness of the film obtained by lamination is 0.5 mm.

[0031] Furthermore, the number of layers of the shear hardening precursor Kevlar prepreg is 25 to 75.

[0032] Furthermore, the conditions for the hot pressing molding are 120° C., 20 MPa, and the pressing time is 20 min.

[0033] Compared with the prior art, the beneficial technical effects of the present invention are:

[0034] The present invention forms a multifunctional flexible composite protective structure that is lightweight, flexible, bulletproof, and infrared heat radiation blocking, and sprays a layer of fluorocarbon resin on the surface of the composite protective structure to enhance the weather resistance of the flexible composite protective structure. The KNA / PEG film has an ultra-low infrared transmittance characteristic and plays a role in infrared heat radiation blocking, the KNA film plays a role in isolating external heat and reducing internal and external heat transfer, the silica aerogel composite fiber felt plays a role in blocking internal heat, and the shear hardener / aramid composite fabric plays a role in bulletproof and impact resistance. The flexible composite protective structure of the present invention ultimately achieves the goal of blocking human body heat transfer and limiting infrared heat radiation emission, making the target temperature consistent with the external environment under infrared thermal imaging, which can improve the stealth and safety of individual combat.

[0035] Aramid nanofiber aerogel membrane is made of high-performance aramid fiber through the "sol-gel-drying" process, which overcomes the disadvantage of low strength of traditional aerogel materials to a certain extent, and is easy to be compounded with temperature phase change materials to prepare nanofiber aerogel phase change composite membrane (KNA / PEG) with excellent heat storage performance and low infrared emissivity. The silicon dioxide aerogel composite fiber felt has a variety of silicon sources and is prepared by the "gel-sol" and atmospheric pressure drying process. The production cost is low, and it can have excellent thermal insulation performance when compounded with fiber felt. It can effectively block human body heat when applied to individual infrared stealth equipment. The surface infrared thermal radiation is limited by the KNA / PEG composite film and kept consistent with the ambient background temperature, realizing the infrared stealth of the human body. The shear hardening / aramid protective main structure behaves as a viscous fluid or elastomer when static or under low strain rate loads. When subjected to high strain rate loads, the material changes phase to a solid state, thereby absorbing a large amount of impact energy and improving protective performance. By evenly dispersing the shear hardening glue in the aramid fiber, the hardness of the aramid fiber interacts with the shear hardening glue, and the impact resistance and energy dissipation level are improved, which is better than the impact resistance of the shear hardening glue alone.

[0036] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram of a multifunctional flexible composite protective structure of the present invention.

[0038] Figure 2 Schematic diagram of the structure of the nanofiber aerogel membrane of the present invention.

[0039] Figure 3 It is a schematic diagram of the structure of the nanofiber aerogel phase change composite membrane of the present invention.

[0040] Figure 4 It is a schematic diagram of the structure of the silica aerogel composite fiber felt of the present invention.

[0041] Figure 5 This is a schematic structural diagram of the shear hardening / aramid protective main structure of the present invention (Figure a is the overall structure, and Figure b is a partially enlarged structure).

[0042] Figure 6 This is a schematic diagram of the stacking of the shear hardening / aramid protection main body structure of the present invention.

[0043] Figure 7 This is a diagram of the infrared thermal radiation blocking mechanism of the multifunctional flexible composite protective structure of the present invention.

[0044] Figure 8 This is a diagram of the infrared thermal radiation blocking mechanism of the nanofiber aerogel phase change composite film of the present invention.

[0045] Fig. 9 This is a diagram of the thermal insulation mechanism of the aerogel of the present invention. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection that the present invention is intended to protect.

[0047] In addition, unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0048] Example 1

[0049] A method for preparing a multifunctional flexible composite protective structure comprises the following steps:

[0050] 1) Preparation method of nanofiber aerogel membrane (KNA):

[0051] Aramid staple fibers are dispersed in a dimethyl sulfoxide solution at a mass ratio of 2:98, and then potassium hydroxide of 1% by mass of the mixed solution is added to form an alkaline environment, making the solution strongly alkaline. The strong alkaline environment causes the H in the aromatic amide bond to be removed, so that the aramid fiber forms a polyanion, the gradual reduction of intermolecular hydrogen bonds and the weakening of π-π bond accumulation lead to a further increase in repulsive force, and the aramid fiber gradually dissociates to form nanofibers, thereby increasing the reaction area, promoting the decomposition of the original fiber, and finally causing the decomposition product to be dispersed in the DMSO solvent. The mixed solution is stirred for 5 to 9 days, and a deep red nanofiber dispersion is obtained after a sufficient sol process. The nanofiber dispersion is scraped to form a sol film, and then immersed in deionized water for replacement to form a gel film, and the residual dimethyl sulfoxide and protonate are removed, and then immersed in a mixed solution of deionized water and tert-butyl alcohol for solvent replacement to obtain a nanofiber hydrogel. Then, the nanofiber aerogel film is obtained after freeze drying for 48 to 72 hours.

[0052] Freeze drying ensures that the gel material completes the sublimation of the internal solvent in a frozen state. During the drying process, the solvent freezes into ice to maintain the spatial structure of the gel. The ice crystals in the hydrogel are sublimated through vacuum to obtain aramid nanofiber aerogel material. Freeze drying is more convenient and efficient than typical supercritical drying.

[0053] See attached Figure 2, which is a schematic diagram of a nanofiber aerogel membrane. The nanofiber aerogel membrane prepared by the preparation method of the present invention has smaller crystal size and more uniform morphology.

[0054] 2) Preparation method of nanofiber aerogel phase change composite membrane (KNA / PEG):

[0055] The nanofiber aerogel membrane obtained in step 1) is placed in a thermal phase change material PEG 10k in a high-temperature molten state, and the PEG is fully adsorbed by the microscopic capillary force of the KNA film. After cooling, a nanofiber aerogel phase change composite membrane is obtained.

[0056] Because the aramid nanofiber aerogel film has good flexibility, high porosity, excellent thermal insulation performance and extraordinary capillary force, it can more fully adsorb PEG, making the nanofiber aerogel phase change composite film have better thermal insulation performance.

[0057] 3) Preparation method of silica aerogel composite fiber felt:

[0058] Mix ethyl orthosilicate, anhydrous ethanol and deionized water in a molar ratio of 1:8:4, add dilute hydrochloric acid to adjust the pH value to 3-4, and carry out hydrolysis reaction at 30°C for 4 hours. After the hydrolysis is completed, add diluted ammonia water in a volume ratio of concentrated ammonia water: anhydrous ethanol of 1:30 to adjust the solution pH value to 6-7 for polycondensation reaction. Before gelation, add 1-3 mm thick aluminum silicate ceramic fiber felt until it is completely soaked, stir for 15 minutes and seal the container to form gel.

[0059] The formed gel was immersed in a sufficient mixed solution of tetraethyl orthosilicate and anhydrous ethanol at 30°C for aging, and the volume ratio of tetraethyl orthosilicate to anhydrous ethanol during aging was 1:5. The aged gel was immersed in anhydrous ethanol for replacement for 30 hours, and then the replaced gel was immersed in a sufficient amount of modification liquid for modification for 20 hours. The modification liquid was a mixture of hexamethyldisilazane and anhydrous ethanol with a volume ratio of 1:5. During the modification process, the hydrophobic groups continuously replaced the hydrophilic groups in the gel to enhance the network structure of the gel. The modified gel was immersed in anhydrous ethanol for replacement for 30 hours again, and then the replaced gel was placed in a normal pressure drying oven and dried by a temperature gradient method, gradually increasing the temperature and then drying slowly at a constant temperature to reduce the destructive force on the wet gel during drying, and a silica aerogel composite fiber felt was obtained.

[0060] See attached Figure 4 , is a schematic diagram of the structure of silica aerogel composite fiber felt. The aerogel is tightly wrapped on the fiber felt to form a good overall structure.

[0061] 4) Preparation method of shear hardening / aramid protective main structure (SSE / Kevlar):

[0062] After fully dissolving the boric acid with isopropanol, add hydroxy silicone oil to the boric acid solution at a ratio of 50 mg / ml and stir evenly, then heat at 180°C for 30 min to volatilize the isopropanol. During this period, stir every 5 min to maintain the reaction uniformity. After volatilization, place in a vacuum kneader and perform polymerization at a high temperature of 220°C for 2 h. When the mixture becomes a viscous polymer with a silk-like luster, a shear hardening glue (SSG) is obtained.

[0063] The prepared shear hardening rubber was mixed evenly with methyl vinyl silicone rubber and benzoyl peroxide in an open rubber mixer at a mass ratio of 70:30:1. 15% of the mass of white carbon black was added during the mixing process. After mixing evenly, a film with a thickness of 0.5 mm was formed at 60° C. using a film press.

[0064] The obtained film is laid flat on the surface of the Kevlar braid and compacted by double rollers to obtain the shear hardening precursor Kevlar prepreg, which is then laid and stacked at variable angles between layers. The number of layers is 50 and hot-pressed at 120°C and 20 MPa for 20 minutes to obtain the shear hardening / aramid protective main structure.

[0065] See attached Figure 6 (a), when stacking, the shear hardening precursor Kevlar prepreg is stacked at an angle of 15° to form a shear hardening / aramid protective main structure, specifically: the shear hardening adhesive reinforced flexible fabric composite material is stacked at an angle of 15°, 50 layers are stacked, and a shear hardening / aramid protective main structure is formed. Since the orthogonal braid has obvious directionality, in order to enhance the protective performance of the protective main structure, multiple layers of shear hardening precursor Kevlar prepreg are stacked at a certain angle, and the adjacent two layers of prepreg are offset at an angle during the stacking process to form a flexible protective layer to disperse and transfer stress.

[0066] 5) Preparation of multifunctional flexible composite protective structure:

[0067] The nanofiber aerogel membrane, nanofiber aerogel phase change composite membrane, silica aerogel composite fiber felt, and shear hardening / aramid protective main structure obtained in steps 1), 2), 3), and 4) are sprayed between adjacent layers using a fluorocarbon resin mixed with B1540 curing agent in the order of shear hardening / aramid protective main structure, silica aerogel composite fiber felt, nanofiber aerogel membrane, and nanofiber aerogel phase change composite membrane, and a multifunctional flexible composite protective structure is obtained after curing and molding.

[0068] Fluorocarbon resin, with its strong CF bond as the skeleton, has the advantages of weather resistance, heat resistance, cold resistance, and chemical resistance. After being mixed with B1540 curing agent and sprayed, the composite protective structure formed is lightweight, flexible, bulletproof, and infrared heat radiation blocking.

[0069] Example 2

[0070] A method for preparing a multifunctional flexible composite protective structure comprises the following steps:

[0071] 1) Preparation method of nanofiber aerogel membrane (KNA):

[0072] Aramid staple fibers are dispersed in a dimethyl sulfoxide solution at a mass ratio of 1.5:98.5, and then potassium hydroxide (1% by mass of the mixed solution) is added to form an alkaline environment, making the solution strongly alkaline, promoting the decomposition of the original fibers, and finally causing the decomposition products to be dispersed in the DMSO solvent. The mixed solution is stirred for 5 to 9 days, and a deep red nanofiber dispersion is obtained after a sufficient sol process. The nanofiber dispersion is scraped to form a sol film, and then immersed in deionized water for replacement to form a gel film, and the residual dimethyl sulfoxide and protonate are removed, and then immersed in a mixed solution of deionized water and tert-butyl alcohol for solvent replacement to obtain a nanofiber hydrogel. Then, the nanofiber aerogel film is obtained after freeze drying for 48 to 72 hours.

[0073] 2) Preparation method of nanofiber aerogel phase change composite membrane (KNA / PEG):

[0074] The nanofiber aerogel membrane obtained in step 1) is placed in a thermal phase change material PEG 10k in a high-temperature molten state, and the PEG is fully adsorbed by the microscopic capillary force of the KNA film. After cooling, a nanofiber aerogel phase change composite membrane is obtained.

[0075] 3) Preparation method of silica aerogel composite fiber felt:

[0076] Mix isopropyl orthosilicate, anhydrous ethanol and deionized water in a molar ratio of 1:10:3, add dilute hydrochloric acid to adjust the pH value to 3-4, and carry out hydrolysis reaction at 35°C for 4 hours. After the hydrolysis is completed, add diluted ammonia water in a volume ratio of concentrated ammonia water: anhydrous ethanol of 1:30 to adjust the solution pH value to 6-7 for polycondensation reaction, add 1-3 mm thick aluminum silicate ceramic fiber felt before gelation until it is completely soaked, stir for 15 minutes and seal the container to form gel.

[0077] The formed gel was immersed in a sufficient mixed solution of isopropyl orthosilicate and anhydrous ethanol at 35°C for aging. The volume ratio of isopropyl orthosilicate to anhydrous ethanol was 1:5 during aging. The aged gel was immersed in anhydrous ethanol for replacement for 30 hours, and then the replaced gel was immersed in a sufficient amount of modification liquid for modification for 24 hours. The modification liquid was a mixture of dimethyldichlorosilane and anhydrous ethanol with a volume ratio of 1:5. During the modification process, the hydrophobic groups continuously replaced the hydrophilic groups in the gel to enhance the network structure of the gel. The modified gel was immersed in anhydrous ethanol for replacement for 30 hours again, and then the replaced gel was placed in a normal pressure drying oven and dried by a temperature gradient method. The temperature was gradually increased and then dried slowly at a constant temperature to reduce the destructive force on the wet gel during drying, and a silica aerogel composite fiber felt was obtained.

[0078] 4) Preparation method of shear hardening / aramid protective main structure (SSE / Kevlar):

[0079] After the boric acid is fully dissolved in isopropanol, hydroxy silicone oil is added to the boric acid solution at a ratio of 50 mg / ml and stirred evenly, and then heated at 200°C for 30 minutes to volatilize the isopropanol. During this period, the mixture is stirred every 5 minutes to maintain the uniformity of the reaction. After the volatilization is completed, it is placed in a vacuum kneader and polymerized at a high temperature of 220°C for 2 hours. When the mixture becomes a viscous polymer with a silk-like luster, a shear hardening glue (SSG) is obtained.

[0080] The prepared shear hardening rubber was mixed evenly with methyl vinyl silicone rubber and benzoyl peroxide in an open rubber mixer at a mass ratio of 70:30:1. 15% of the mass of white carbon black was added during the mixing process. After mixing evenly, a film with a thickness of 0.5 mm was formed at 60° C. using a film press.

[0081] The obtained film is laid flat on the surface of the Kevlar braid and compacted by double rollers to obtain the shear hardening precursor Kevlar prepreg, which is then laid and stacked at variable angles between layers. The number of layers is 50 and hot-pressed at 120°C and 20 MPa for 20 minutes to obtain the shear hardening / aramid protective main structure.

[0082] See attached Figure 6 (b) When stacking, the shear hardening precursor Kevlar prepreg is stacked at an offset angle of 30° to form a shear hardening / aramid protective main structure.

[0083] 5) Preparation of multifunctional flexible composite protective structure:

[0084] The nanofiber aerogel membrane, nanofiber aerogel phase change composite membrane, silica aerogel composite fiber felt, and shear hardening / aramid protective main structure obtained in steps 1), 2), 3), and 4) are sprayed between adjacent layers using a fluorocarbon resin mixed with B1540 curing agent in the order of shear hardening / aramid protective main structure, silica aerogel composite fiber felt, nanofiber aerogel membrane, and nanofiber aerogel phase change composite membrane, and a multifunctional flexible composite protective structure is obtained after curing and molding.

[0085] Example 3

[0086] A method for preparing a multifunctional flexible composite protective structure comprises the following steps:

[0087] 1) Preparation method of nanofiber aerogel membrane (KNA):

[0088] Aramid staple fibers are dispersed in a dimethyl sulfoxide solution at a mass ratio of 2.5:97.5, and then potassium hydroxide (1% by mass of the mixed solution) is added to form an alkaline environment, making the solution strongly alkaline, promoting the decomposition of the fibrils, and finally causing the decomposition products to be dispersed in the DMSO solvent. The mixed solution is stirred for 5 to 9 days, and a deep red nanofiber dispersion is obtained after a sufficient sol process. The nanofiber dispersion is scraped to form a sol film, and then immersed in deionized water for replacement to form a gel film, and the residual dimethyl sulfoxide and protonate are removed, and then immersed in a mixed solution of deionized water and tert-butyl alcohol for solvent replacement to obtain a nanofiber hydrogel. Then, the nanofiber aerogel film is obtained after freeze drying for 48 to 72 hours.

[0089] 2) Preparation method of nanofiber aerogel phase change composite membrane (KNA / PEG):

[0090] The nanofiber aerogel membrane obtained in step 1) is placed in a thermal phase change material PEG 10k in a high-temperature molten state, and the PEG is fully adsorbed by the microscopic capillary force of the KNA film. After cooling, a nanofiber aerogel phase change composite membrane is obtained.

[0091] 3) Preparation method of silica aerogel composite fiber felt:

[0092] Methyl orthosilicate, anhydrous ethanol and deionized water were mixed in a molar ratio of 1:6:6, and diluted hydrochloric acid was added to adjust the pH value to 3-4. The hydrolysis reaction was carried out at 25°C for 4 hours. After the hydrolysis was completed, diluted ammonia water was added in a volume ratio of concentrated ammonia water: anhydrous ethanol of 1:30 to adjust the pH value of the solution to 6-7 for polycondensation reaction. Before gelation, 1-3 mm thick aluminum silicate ceramic fiber felt was added until it was completely soaked, stirred for 15 minutes and the container was sealed to form a gel.

[0093] The formed gel was immersed in a sufficient mixed solution of methyl orthosilicate and anhydrous ethanol at 25°C for aging, and the volume ratio of methyl orthosilicate to anhydrous ethanol during aging was 1:5. The aged gel was immersed in anhydrous ethanol for replacement for 30 hours, and then the replaced gel was immersed in a sufficient amount of modification liquid for modification for 20 hours. The modification liquid was a mixture of hexamethyldisilazane and anhydrous ethanol with a volume ratio of 1:5. During the modification process, the hydrophobic groups continuously replaced the hydrophilic groups in the gel to enhance the network structure of the gel. The modified gel was immersed in anhydrous ethanol for replacement for 30 hours again, and then the replaced gel was placed in a normal pressure drying oven and dried by a temperature gradient method, gradually increasing the temperature and then drying slowly at a constant temperature to reduce the destructive force on the wet gel during drying, and a silica aerogel composite fiber felt was obtained.

[0094] 4) Preparation method of shear hardening / aramid protective main structure (SSE / Kevlar):

[0095] After fully dissolving the boric acid with isopropanol, add hydroxy silicone oil to the boric acid solution at a ratio of 50 mg / ml and stir evenly, then heat at 180°C for 30 min to volatilize the isopropanol. During this period, stir every 5 min to maintain the reaction uniformity. After volatilization, place in a vacuum kneader and perform polymerization at a high temperature of 220°C for 2 h. When the mixture becomes a viscous polymer with a silk-like luster, a shear hardening glue (SSG) is obtained.

[0096] The prepared shear hardening rubber was mixed evenly with methyl vinyl silicone rubber and benzoyl peroxide in an open rubber mixer at a mass ratio of 70:30:1. 15% of the mass of white carbon black was added during the mixing process. After mixing evenly, a film with a thickness of 0.5 mm was formed at 60° C. using a film press.

[0097] The obtained film is laid flat on the surface of the Kevlar braid and compacted by double rollers to obtain the shear hardening precursor Kevlar prepreg, which is then laid and stacked at variable angles between layers. The number of layers is 50 and hot-pressed at 120°C and 20 MPa for 20 minutes to obtain the shear hardening / aramid protective main structure.

[0098] See attached Figure 6 (a) During stacking, the shear hardening precursor Kevlar prepreg is stacked at an offset angle of 15° to form a shear hardening / aramid protective main structure.

[0099] 5) Preparation of multifunctional flexible composite protective structure:

[0100] The nanofiber aerogel membrane, nanofiber aerogel phase change composite membrane, silica aerogel composite fiber felt, and shear hardening / aramid protective main structure obtained in steps 1), 2), 3), and 4) are sprayed between adjacent layers using a fluorocarbon resin mixed with B1540 curing agent in the order of shear hardening / aramid protective main structure, silica aerogel composite fiber felt, nanofiber aerogel membrane, and nanofiber aerogel phase change composite membrane, and a multifunctional flexible composite protective structure is obtained after curing and molding.

[0101] The infrared heat radiation blocking principle of the multifunctional flexible composite protective structure of the present invention is as follows:

[0102] See attached Figure 7 , 8 , the silica aerogel composite fiber felt forms a stable fiber network structure, and the silica aerogel is tightly wrapped on the fiber felt to form two network structures. While ensuring the stability of the material structure, it has good thermal insulation performance. The complex nanopores effectively weaken the gas phase conduction, and cannot form heat convection, and extend the heat transfer path, which has a certain barrier effect on the temperature and has a good thermal insulation effect. The nanofiber aerogel membrane forms a nanoscale porous three-dimensional grid structure with a complex distribution, a small pore size, and extends the heat transfer route. The aramid nanofiber itself has a strong thermal insulation and antioxidant effect, which can withstand the high temperature of 300 degrees Celsius in the outer layer, and has a good barrier effect on thermal radiation, and has a good thermal insulation effect. The present invention uses the silica aerogel composite fiber felt and the nanofiber aerogel membrane in combination. After two-stage thermal insulation, the thermal insulation effect is better. The silica aerogel composite fiber felt is mainly used for human body heat blocking, and the nanofiber aerogel membrane is mainly used for external environmental heat blocking.

[0103] After the nanofiber aerogel phase change composite membrane is treated with phase change materials, PEG 10k will store heat and soften when heated, and release heat and harden again when solidified. This means that when in use, when the ambient temperature is high, the composite membrane absorbs heat in the environment to suppress temperature rise, and when the ambient temperature drops, the composite membrane can slowly release the stored heat to match the ambient temperature. Therefore, when very little human body heat is transferred to the nanofiber aerogel phase change composite membrane, the nanofiber aerogel phase change composite membrane can achieve infrared stealth by regulating temperature, and it also has a certain infrared reflection function, achieving stealth function under infrared irradiation.

[0104] The impact resistance principle of a multifunctional flexible composite protective structure of the present invention is as follows:

[0105] The shear hardening / aramid protective main structure evenly disperses the shear hardening glue in the aramid fiber. Under the natural state, most of the BO bonds in the shear hardening glue are broken (Formula I), and the shear hardening / aramid protective main structure exhibits a viscoplastic state with typical cold flow characteristics; at the beginning of the impact, under external impact, BO bonds begin to form in the shear hardening glue, and the number of BO bonds gradually increases (Formula II), the viscosity and modulus of the shear hardening / aramid protective main structure increase rapidly, the strain rate related parameters are enhanced, and the impact resistance is enhanced; when the impact weakens, the BO bonds in the shear hardening glue begin to break, and the number of BO bonds gradually decreases (Formula III), the viscosity and modulus of the shear hardening / aramid protective main structure gradually decrease, and the impact resistance is weakened; after the impact is completed, the impact effect is lost, most of the BO bonds in the shear hardening glue are broken (Formula I), and the viscoplastic state is restored. The present invention evenly disperses the shear hardening glue in the aramid fiber, and the hardness of the aramid fiber interacts with the shear hardening glue, so that the impact resistance and energy dissipation level are improved, which is better than the impact resistance of the shear hardening glue alone.

[0106]

[0107] The KNA / PEG film in the present invention has the characteristics of ultra-low infrared transmittance and plays a role in blocking infrared thermal radiation. The KNA film plays a role in isolating external heat and reducing internal and external heat transfer. The silica aerogel composite fiber felt plays a role in blocking internal heat. The shear hardener / aramid composite fabric plays a role in bulletproof and impact resistance. The flexible composite protective structure can ultimately block the heat transfer of the human body and limit the emission of infrared thermal radiation. Under infrared thermal imaging, the temperature of the target is consistent with that of the external environment, which can improve the stealth and safety of individual combat.

[0108] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.

[0109] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A multifunctional flexible composite protective structure, characterized in that: The composite protective structure comprises, from the outer layer to the inner layer, a nanofiber aerogel phase change composite film (KNA / PEG), a nanofiber aerogel film (KNA), a silica aerogel composite fiber felt, and a shear hardening / aramid (SSE / Kevlar) protective main body structure. The shear hardening / aramid protective main body structure is obtained by stacking multiple layers of shear hardening precursor Kevlar prepreg and then heat treating them.

2. The method for preparing a multifunctional flexible composite protective structure according to claim 1, characterized in that: The method comprises the following steps: arranging a nanofiber aerogel phase change composite film, a nanofiber aerogel film, a silica aerogel composite fiber felt, and a shear hardening / aramid protective main structure in sequence, spraying a fluorocarbon resin mixed with a B1540 curing agent between the layers, and curing and forming the mixture to obtain the composite film; The nanofiber aerogel phase change composite film is obtained by melting the thermal phase change material PEG at high temperature and adsorbing it through the microscopic capillary force of the KNA film; The shear hardening / aramid protective main structure is prepared by uniformly mixing the prepared shear hardening glue with methyl vinyl silicone rubber and a vulcanizer, adding white carbon black and pressing the film at 60°C, laying the obtained film flat on the surface of the Kevlar braid and compounding it with double rollers to obtain a shear hardening precursor Kevlar prepreg, and then obtaining it through variable angle laying and stacking between layers and hot pressing molding.

3. A method for preparing a multifunctional flexible composite protective structure as claimed in claim 2, characterized in that: The preparation method of the nanofiber aerogel membrane is as follows: aramid short fibers are dispersed in a dimethyl sulfoxide solution, a strong base is added to form an alkaline environment, a nanofiber dispersion is obtained after a sufficient sol process, a nanofiber hydrogel is obtained after replacement with deionized hydrogel, anhydrous ethanol and tert-butyl alcohol, and then a nanofiber aerogel membrane is obtained after freeze-drying.

4. A method for preparing a multifunctional flexible composite protective structure as claimed in claim 3, characterized in that: The mass ratio of the added aramid staple fibers to dimethyl sulfoxide is 1.5-2.5:97.5-98.

5.

5. The method for preparing a multifunctional flexible composite protective structure according to claim 3, characterized in that: The nanofiber dispersion is scraped to form a sol film, then immersed in deionized water for replacement to form a gel film, and the residual dimethyl sulfoxide and protonate are removed, and then enters a mixed solution of anhydrous ethanol and tert-butyl alcohol for solvent replacement to obtain a nanofiber hydrogel.

6. A method for preparing a multifunctional flexible composite protective structure as claimed in claim 2, characterized in that: The preparation method of the silica aerogel composite fiber felt is as follows: a silicon source, anhydrous ethanol and deionized water are mixed in proportion and the pH value is adjusted to 3-4 to carry out a hydrolysis reaction; after the hydrolysis is completed, the pH value of the solution is adjusted to 6-7 to carry out a condensation reaction; before gelation, aluminum silicate ceramic fiber felt is added and placed in a closed container to form a gel; and the gel is aged, replaced, modified, replaced and dried to obtain the silica aerogel composite fiber felt.

7. A method for preparing a multifunctional flexible composite protective structure as claimed in claim 6, characterized in that: The molar ratio of the silicon source to anhydrous ethanol and deionized water is 1:6-10:2-6.

8. The method for preparing a multifunctional flexible composite protective structure according to claim 6, characterized in that: The gel aging is to immerse the formed gel in a mixed solution of sufficient silicon source and anhydrous ethanol, and the volume ratio of the silicon source to the anhydrous ethanol during aging is 1:

5.

9. The method for preparing a multifunctional flexible composite protective structure according to claim 6, characterized in that: The replacement is to immerse the aged gel in anhydrous ethanol, and the modification is to put the replaced gel into a sufficient amount of modification liquid for modification for 8 to 24 hours. The modification liquid is a mixture of a modifier and anhydrous ethanol, and the modifier is hexamethyldisilazane, trimethylchlorosilane, dimethyldichlorosilane, and methyltrichlorosilane.

10. The method for preparing a multifunctional flexible composite protective structure according to claim 2, characterized in that: The preparation method of the shear hardening glue is as follows: after fully dissolving boric acid with isopropanol, adding hydroxy silicone oil and stirring evenly, then heating at 150-200° C. to volatilize the isopropanol, placing the mixture in a vacuum kneader for polymerization reaction after the volatilization is completed, and obtaining the shear hardening glue after the mixture becomes a viscous polymer with a silk-like luster.

Citation Information

Patent Citations

  • Preparation method of hydrophobic silica aerogel composite fiber felt material

    CN108569912A

  • Aerogel-based host-guest composite film and preparation method and application thereof

    CN113527761A

  • Preparation method of flexible protection structure with heat insulation, flame retardance and self-cleaning performance

    CN113756100A

  • Preparation method of thermal shock resistant aramid fiber aerogel and aramid fiber aerogel

    CN117362743A